Problems and analysis directions in smart grid technology and their potential solutions - Manoj Saini; Shagufta Khan; Rajeev Gupta; Shivani Singh; Pooja Upadhyay; Shivangi Soni (Institute of Advanced Engineering and Science, 2021)
The idea of smart grid (SG) technology has revolutionized the traditional power system and has made it more efficient, robust and reliable in a number of ways. SG networks are recently upgraded networks of associated objects of information and communication technology (ICT) and core technology. Many active research areas have been developed to achieve the goals and planned requirements of the transfer of power systems from the traditional grid to the SG. Despite the significant characteristics of SG, future research needs to resolve numerous problems relating to core and ICT technology. This analysis paper identifies the challenges facing SG growth, potential research directions and also proposes possible solutions to some of these challenges, thus achieving the SG goals and planned requirements.